Physical condition improvement in elite volleyball players - Malikov, N.; Konoh, A.; Korobeynikov, G.; Korobeynikova, L.; Dudnyk, O.; Ivaschenko, E. (Journal of Physical Education and Sport, 2020)
Purpose: to substantiate scientifically the content of the program of planning training sessions and increase the level of functional and special physical condition of elite volleyballers. Material: The pedagogical study was attended by 14 elite female athletes specializing in volleyball. The study recorded indicators of functional and special physical condition. Results: The use of the proposed training program in the training process contributed to maintaining during the competitive period the optimal level of functional and special physical condition of female athletes: a significant (p<0,001) decrease in their indicators by the end of the competitive period was only 3-15%, while using the traditional program was significantly higher (5-50%). After the competition period, all indicators of the athletes' special physical preparedness were in line with the average level. The level of functional preparedness of the surveyed female athletes at the end of the competition period was significantly (p<0,001) reduced and considered as below average. Conclusions: While designing new programs for constructing a training process for elite athletes, it is necessary to take into account the dynamics of functional and special condition in individual microcycles, the nature of the correlation between the level of functional condition and its individual components, indicators of special physical preparedness and organization on the basis of this that enables purposeful management of the training process. It was determined that the use of volleyball players in the training process of our training program, which provided for the presence of competitive and corrective modules, dependence of their content on the results of pre-testing contributed to the maintenanc of the optimal level of indicators of functional and special physical condition of female athletes throughout the competitive period.